Worldwide survey of flexible ureteroscopy practice: a survey from European Association of Urology sections of young academic urologists and uro-technology groups - ŞENER, TARIK EMRE (POLISH UROLOGICAL ASSOC, 2019)
Introduction To understand the current practice of flexible ureteroscopy (fURS), we conducted a worldwide survey among urologists with a special interest in endourology. Material and methods A 42-question survey was designed after an initial consultation with European Association of Urology young academic urologists (YAU) and uro-technology (ESUT) groups. This was distributed via the SurveyMonkey (R) platform and an ESUT meeting to cover practice patterns and techniques in regard to ureteroscopy usage worldwide. Results A total of 114 completed responses were obtained. A safety guidewire was reportedly used by 84.5% of endourologists, an access sheath was always or almost always used by 71% and a reusable laser fibre was used by two-thirds of respondents. While a combination of dusting and fragmentation was used by 47% as a preferred mode of intra-renal stone treatment, some used dusting (43%) or fragmentation with basketing (10%). Disposable scopes were only used by 40% and three quarters of them used it for challenging cases only. Antibiotic prophylaxis was limited to a single peri-operative dose by two-thirds (67%) of respondents. The procedural time was limited to between 1-2 hours by two-thirds (70%) of respondents and very rarely (7.4%) it exceeded 2 hours. The irrigation method varied between manual pump (46%), mechanical irrigation (22%) or gravity irrigation (27%). Conclusions Our survey shows a wide variation in the available endourological armamentarium and surgical practice amongst urologists. However, there seems to be a broad agreement in the use of peri-operative antibiotics, access sheath usage, method of stone treatment and the use of post-operative stent.
Keywords: survey; ureteroscopy; endourology; urolithiasis; laser; stone; flexible; access sheath; fragmentation; STONE DISEASE; COMPLICATIONS; UROLITHIASIS; TRENDS; ULTRA; COST